Improving measles vaccination coverage in South Sudan: The necessity to adopt a coordinated and multisectoral approach - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Medical Journal of Babylon, 2020)
Measles is a life-threatening infectious disease, accounting for the deaths of more than 140,000 deaths worldwide in 2018. It is worth noting that the incidence of the disease is extremely high in the low- and middle-income nations, which are having multiple other competing public health priorities, a weak health-care delivery system, or ongoing humanitarian emergencies. South Sudan has been subjected to long-term conflicts, and with regard to measles, it has been reported that more than 4700 cases and 26 deaths have been reported in the nation since the disease outbreak began last year. Keeping this in mind and in order to avert fatal consequences and accomplish 95% vaccine coverage, the international welfare agencies have joined their hands together and initiated a vaccination drive to immunize 2.5 million children across the entire nation along with the provision of Vitamin A and deworming tablets. In conclusion, considering the fact that measles is vaccine preventable and every child deserves the right to receive the vaccine, it is high time that we take necessary steps to ensure political leadership, strengthening of health facilities, and involvement of the parents so that the planned vaccination campaign can accomplish the intended results in the conflict-affected South Sudan.